Long-term endocrinological outcomes of gamma knife radiosurgery in acromegaly patients - YAVUZ, DİLEK (CHURCHILL LIVINGSTONE, 2020)
Gamma knife radiosurgery (GKS) is a treatment option for recurrent or persistent disease in patients with acromegaly. Objective: We aimed to retrospectively evaluate acromegaly patients who had undergone GKS in terms of pituitary hormone status, efficacy of GKS, and prognostic factors. Method: One-hundred and ten acromegaly patients who underwent GKS, and who were referred to our outpatient endocrinology clinic between 2007 and 2017, were included in the study. Anterior pituitary hormones and radiology imaging during follow-up were recorded. Remission for acromegaly was defined as a normal insulin-like growth factor 1 (IGF-1) level adjusted for age and gender, and a random growth hormone (GH) level < 1 ng/ml. Endocrine control was defined as normal GH and IGF-1 levels under medication. Results: After a mean follow-up of 6.5 4.7 years; remission, endocrine control, and uncontrolled status was observed in 16.4%, 60%, and 23.6% of patients; respectively. Adenoma volume was decreased after GKS (P < .0001). Remnant adenoma diameter was higher in the uncontrolled group compared to the remission and endocrine control group. The presence of tumor extension was associated with disease status (P = .03) and higher initial GH and IGF-1 levels. The mean time after GKS to remission was 26.5 months. Six (5.4%) patients had new-onset pituitary deficiency after GKS. In the multivariate analysis, pre-GKS IGF-1 levels and patient's age were associated with disease status. Conclusion: GKS is an effective adjuvant treatment with minimal side effects to control GH and IGF-1 levels, increase remission rates, endocrine control, and reduce tumor diameter in persistent acromegaly patients after surgery.
Keywords: Acromegaly; Gamma knife radiosurgery; Growth hormone; Endocrine outcomes; Pituitary adenoma; Panhypopituitarism; IGF-1; STEREOTACTIC RADIOSURGERY; CONSENSUS; CRITERIA; SOCIETY; CURE